Investigating the Role of Green Accounting, Firm Size, and Board Size in Corporate Social Responsibility: Towards Sustainable Transparency Disclosure - Mumtaz Jiddan; Dini Wahjoe Hapsari (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The objective of this study is to examine the influence of green accounting, firm size, and board size on corporate social responsibility disclosure in primary consumer sector companies listed on the IDX for the period of 2021–2022. Green accounting, firm size, and board size are considered as independent variables, while corporate social responsibility disclosure is the dependent variable under investigation. This research employs both descriptive and verificative research methodologies, and the sample consists of 120 consumer sector companies listed on the IDX during the specified period. The purposive sampling technique is utilized to select a final sample size of 45 companies. The Eviews program was used for panel data regression in the employed data analysis technique. The research data is based on secondary sources, specifically annual reports and sustainability reports. The findings indicate that board size has a negative impact on corporate social responsibility disclosure, whereas green accounting and firm size do not demonstrate any significant influence.